Efektivitas Ekstrak Etanol Daun Bayam Merah sebagai Hepatoprotektor terhadap Kadar ALP Serum Mencit yang Diinduksi Isoniazid (Hepatoprotective Activity of Red Spinach (Amaranthus tricolor L.) Leaves Ethanolic Extract on ALP Serum Mice Induced by Isoniazi - Shinta Madyaning Wuri; Aris Prasetyo; Elly Nurus Sakinah (UPT Percetakan dan Penerbitan Universitas Jember, 2017)
Isoniazid (INH) is metabolized become hidrazine that depleted glutation (GSH) in hepatocytes, resulted imbalance oxidant and antioxidant along with increased of free radicals, which can increase alkaline phosphatase (ALP). Ethanolic extract of red spinach (Amaranthus tricolor L.) leaves contains antioxidant which can donates the electron so free radical can be stabilized. The aim of this study was to investigate the effect of ethanolic extract of red spinach leaves on ALP levels of mice induced by INH and its effective dose. This research used 28 mices that divided into seven groups: K(N) was given normal saline, K(-) was given INH 100 mg/kgBW, K1, K2, K3, K4 and K5 group which given INH 100 mg/kgBW peroral and after 2 hours would be given ethanolic extract of red spinach leaves in the dose 1,05 mg/20gBW, 2,1 mg/20gBW, 4,2 mg/20gBW, 8,4 mg/20gBW and 16,8 mg/20gBW for ten days. ALP serum was measured on the day 11th.The result of average ALP levels were K(N) 41,36 U/L, K(-) 110,97 U/L, K1 79,26 U/L, K2 71,34 U/L, K3 66,51 U/L, K4 62,82 U/L and K5 47,21 U/L. In conclusion the ethanolic extract of red spinach leaves could prevent the increasing of ALP levels and the effective dose of the extract was 6,75 mg/20gBW. Keywords: red spinach leaves, ALP, INH